Effects of Maitland manual therapy on the treatment of pain syndromes of the cervical spine - Dzierżek, Ireneusz; Cichosz, Michał; Czerwiński, Paweł; Wilk, Tomasz; Kałużny, Krystian; Kałużna, Anna; Żukow, Walery (Journal of Education, Health and Sport, 2017)
Introduction: The aim of this study was evaluate the effect of Maitland’s manual therapy on selected motor function parameters in cervical spine pain syndromes. Material and Methods: 30 subjects were enrolled, in the age from 27 to 66, including 15 men and 15 women with chronic functional cervical spine syndrome who had a 10-day physiotherapy cycle that did not produce the expected results. The study included: pain assessment in the Dziak scale, measurements of mobility of the cervical spine and shoulder joints, functional evaluation by Hautanta, De`Klein, Jackson, and palpation of muscle irritation. Results: A comparison of average pain scores before and after therapy indicated that the pain level after treatment decreased (p <0.05), but only in some patients (n = 23). The mean values of cervical vertebrae before and after therapy vary from the dependence on the investigated movement. There is an increase in the range of rotation, straightening and bending to the right in men and women (p <0.05), the range of bending forward and bending left only in women (p <0.05). There was no change in parenchymal mobility in parenchymal tumors (p> 0.05). There has been a decrease in positive clinical trials and muscle irritation after therapy. Conclusions: Maitland manual therapy is effective in the treatment of cervical spine pain syndromes. The technique results in a significant increase in the mobility of the cervical spine as well as an improvement in the functional state of the cervical segment without affecting the mobility of the shoulder ridge. There was a decrease in palpate tenderness of the soft tissue studied.